Accumulation of Salicylic Acid and 12-oxo-phytodienoic Acid Acting on the Antioxidant Pathway to Keep Stability of Striped Leaves of Variegated Temple Bamboo - Chen, Lingyan; Tang, Yu; Tao, Yun; Seerat, Azra; Zhu, Pengkai; He, Tianyou; Zheng, Yushan (Journal of the American Society for Horticultural Science, 2024)
Variegated temple bamboo ( Sinobambusa tootsik f. luteoloalbostriata ) is one of the native variegated bamboo species has some whole green (WG) and whole white (WW) leaves in addition to striped green and white ones. The life span of WW leaves is short, but the life span of striped leaves (SLs) is unaffected by the area of white mesophyll, and the SL phenotype is well maintained. To explore the mechanism of phenotypic stability of SL, we took five leaf phenotypes as study materials: WG, WW, SL, the green part of SL (SG), and the white part of SL (SW). Through the measurement of photosynthetic pigments, leaf nutrient elements, chloroplast synthesis–related hormones and their precursors in the leaves, and antioxidant system parameters, we examined the antioxidant adaptation mechanism of the white mesophyll cells of S. tootsik f. luteoloalbostriata . The results indicated that abscisic acid (ABA) levels were substantially higher in WW leaves than in SW leaves, and salicylic acid (SA) levels were significantly higher in SW leaves compared with WW leaves. Levels of 12-oxo-phytodienoic acid (OPDA), and SA were substantially higher in WW and SW than in the leaves of the other three phenotypes. Glutathione (GSH) levels were substantially higher in SW than in SG and reactive oxygen species (ROS) levels were significantly lower. Overall, the white mesophyll cells of S. tootsik f. luteoloalbostriata had strong antioxidant properties. SA and OPDA jointly act on the antioxidant pathway to reduce the content of ROS in leaves, thus ensuring the stability of SL.